Evidence for two restriction-modification systems in Halobacterium cutirubrum. - Patterson, N H (1985)
Data from plating experiments indicated that Halobacterium cutirubrum NRC34001 has at least two separate restriction-modification systems. A spontaneous or induced loss of one or both systems resulted in four restriction-modification phenotypes. There was a positive correlation between changes in gas vacuolation phenotypes and either restriction-modification system.